2015
DOI: 10.1161/jaha.114.001504
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Recovery of Normal Left Ventricular Function and Dimension in Idiopathic Dilated Cardiomyopathy During Long‐Term Follow‐up: Does Real Healing Exist?

Abstract: BackgroundAn important number of patients with idiopathic dilated cardiomyopathy have dramatically improved left ventricular function with optimal treatment; however, little is known about the evolution and long‐term outcome of this subgroup, which shows apparent healing. This study assesses whether real healing actually exists in dilated cardiomyopathy .Methods and ResultsPersistent apparent healing was evaluated among 408 patients with dilated cardiomyopathy receiving tailored medical treatment and followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
66
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 31 publications
4
66
1
Order By: Relevance
“…In this regard, it is equally interesting to note that patients with HFmrEF continue to have significant number of HF events, including death, and that the magnitude of these events was not significantly different from patients with HFpEF. The observation that HFmrEF patients with an improved LVEF continue to have recurrent HF events is consistent with prior reports which have shown that recovery of LV function is not necessarily associated with freedom from future HF events . A second unique observation in the present study was that the HFmrEF deteriorated patients had significantly more advanced diastolic dysfunction that the HFmrEF improved subgroup of patients, suggesting that despite having a similar LVEF the underlying pathophysiological substrate of HFmrEF is not uniform and depends on the underlying aetiology of HF.…”
Section: Discussionsupporting
confidence: 90%
“…In this regard, it is equally interesting to note that patients with HFmrEF continue to have significant number of HF events, including death, and that the magnitude of these events was not significantly different from patients with HFpEF. The observation that HFmrEF patients with an improved LVEF continue to have recurrent HF events is consistent with prior reports which have shown that recovery of LV function is not necessarily associated with freedom from future HF events . A second unique observation in the present study was that the HFmrEF deteriorated patients had significantly more advanced diastolic dysfunction that the HFmrEF improved subgroup of patients, suggesting that despite having a similar LVEF the underlying pathophysiological substrate of HFmrEF is not uniform and depends on the underlying aetiology of HF.…”
Section: Discussionsupporting
confidence: 90%
“…This cohort, although large, was enrolled in a single centre and has a relatively low prevalence of common co‐morbidities such as diabetes mellitus. It is possible that this reflects a degree of selection bias; however, our referral base is broad, from specialist and non‐specialist centres and the baseline characteristics are similar to other cohorts . The referral characteristics and specifically the proportion of men and women referred remain stable over the study period (online supplementary Figure S1).…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, deterioration in RVF might reflect the intrinsic progression of the cardiomyopathy process that typically characterizes DCM in the long term (22). The measurement of tricuspid annular plane systolic excursion as a simple parameter of RVF was not considered in our series because it was available only in a minority of patients and its reliability in assessing global RVF is questionable.…”
mentioning
confidence: 99%